Adoption of patient‐reported outcome measures with youth with intellectual/developmental disabilities: Contextual influences and practice patterns. (8th March 2021) - Greenberg, Kimberly K.; Schwartz, Ariel E.; Kramer, Jessica M.
Abstract: Background: The purpose of this study was to identify potential barriers to patient reported outcome measure (PROM) adoption with youth and young adults with intellectual and/or developmental disabilities (IDD) and to understand current PROM adoption patterns of paediatric practitioners working with this population. Methods: We used a web‐based survey to collect data from paediatric practitioners who work with youth with IDD about factors influencing the adoption of PROMs and the frequency of PROM use across age groups (elementary, middle school and high school/transition age) and practice settings (school and rehabilitation). Results: A total of 113 paediatric practitioners (occupational therapist = 48, physical therapist = 32, physician = 16, other = 17) responded to the survey with an average of 15 years of experience working with youth ages 8–21 with IDD. Accessibility and appropriateness, psychometric evidence, and time were most frequently ranked among the top three factors that influence practitioners' adoption of PROMs. Practitioners reported 'never or rarely' using PROMs 39%–65% of the time across age groups. Conclusions: Our results suggest that paediatric practitioners may be infrequently using PROMs with youth with IDD because of perceived inaccessibility and time requirements of PROMs and practice‐environment barriers, including access to evidence and caseload demands. Because PROMs can facilitate client‐centred care, addressing these potential barriers to adoption may improve paediatric rehabilitation.